Barriers to involving GP Speciality Trainees in the teaching of medical students in primary care: the GP trainer perspective. Issue 6 (2nd November 2019) - Harrison, Michael; Alberti, Hugh; Thampy, Harish
ABSTRACT: Involvement in teaching activities is a curriculum requirement for GP Speciality Trainees (GPSTs). There are numerous potential benefits to involving GPSTs in teaching, including mutual educational benefit for both GPST and learner. However, GPSTs on placement in primary care may be less involved in teaching activities than hospital-based trainees. The reasons for this are not fully understood. This multi-site study aimed to explore the perceptions of GP trainers of the barriers to involving GPSTs in teaching in primary care. Focus groups of General Practice (GP) trainers from four regional GP training programmes across Northern England were conducted. Data were analysed thematically. Trainers cited barriers relating to the trainee (e.g. capacity and capability), practice (e.g. capacity), and teaching (e.g. appropriateness of teaching methods). Underlying these barriers, there appeared to be a cultural attitude towards GPST involvement in teaching: trainers viewed teaching as an extraneous rather than integral part of GP training, considered teaching to represent a deviation from the norm and felt that the GPST was restricted to a learner role. Whilst attempts to address the practical barriers identified in this study are required, a cultural shift in which the role of the GPST as a teacher becomes normalised is urgently needed.